Salmonella e outras enterobactérias nas etapas de pós-colheita e beneficiamento do amendoim - Bernardi, Angélica Olivier (2015)
In recent years, peanut has been considered a potential product for Salmonella infection. due to numerous reported outbreaks involving peanut products to the base, however, there is still little information available in the literature on the occurrence of Salmonella sp. in post-harvest processing steps and peanuts. This study aims to determine the prevalence of enterobacteria, coliforms, Escherichia coli and Salmonella sp. during the stages of post-harvest and processing of peanuts. We analyzed 60 samples of producers in the states of São Paulo, Minas Gerais and Bahia involving the steps of pull out, sun drying and picking of the plant and 60 samples from 4 hulling plant in the state of São Paulo, comprising drying steps samples , thrashed, selection and blancheado. The Salmonella survey was conducted in 250 g sample by immunoassay method using the Mini-Vidas system. For enterobacteria analysis, we used the means of Violet Red Bile Agar Glucose (VRBG) and for total coliforms and E. coli Petrifilm. In addition to the microbiological analyzes were also checked the pH and water activity (aw) of the samples. Regarding the microbiological testing, the samples showed high counts of enterobacteria, 6.62 to 8.46 log CFU/g at pull out stage, from 5.18 to 8.36 log CFU/g in sun drying and from 7.31 to 8, 82 log CFU/g in picking. The sun drying stage had the lowest total coliform counts (from 3.68 to 6.01 log CFU/g) followed by picking (from 4.32 to 6.33 log CFU/g) and pull out (5.38 to 6.82 log CFU/g). Two samples showed contamination by E. coli and a sample of the bunching step (2 log CFU/g) and a picking of step (4 log CFU/g). Six samples were contaminated by Salmonella sp, and a sample of the pull out stage of SP (0.064 MPN/g) and five from picking of step (Two of São Paulo – 0.004 MPN/g and three of Minas Gerais - 0.037 to 0.092 MPN/g). The processing step that had the lowest enterobacteria count was to the blancheamento (1.71 to 2.81 log CFU/g). The analyzes were similar to those of coliform enterobacteria, results in higher drying previous step (2.28 to 4.78 log CFU/g) and smaller blancheamento in step (1 to 1.60 CFU/g log), there was E. coli contamination in any of the analyzes during processing stages. Two samples showed the drying step count of Salmonella sp. (0.004 to 0.004 MPN/g). The results show that there may be peanut contamination by Salmonella sp. prior to processing, this reinforces the importance of employing good agricultural practices and manufacturing programs to prevent the presence of this important pathogen in the final product.